Fatty acids in fish and beef and their nutritional values: a review. - Abbas, Kassim Ali; A., Mohamed; Bakar, Jamilah (Wfl Publisher, 2009)
This review aims to summarize the latest developments and recent knowledge regarding the fatty acids in fish and beef, their profiles and nutritional values. The paper covered the types of different fatty acids such as unsaturated fatty acids (UFA), polyunsaturated fatty acids (PUFA), especially the omega-3 in different fish species. The study also summarized the nutritional values of the fatty acids as compared to those in other animal species. However, the strategies influencing the fatty acid composition of beef were also reflected. The study revealed that many fatty fishes were found as excellent sources of UFA and PUFA, especially the omega-3. On the other hand, beef was proposed major source of saturated fat in a diet. The quality attributes of beef meat such as tenderness, juiciness, and flavor intensity have been shown to be affected by the chemical properties and lipid content. Moreover, increasing dietary omega-3 fatty acid intakes for potential health benefits for protecting against cardiovascular diseases was recommended. This work may assist the researchers and scientists to have a clear picture about what have been achieved earlier and what critical work should be conducted in future.